PENERAPAN MODEL PROJECT BASED LEARNING DALAM PENGUATAN KARAKTER GOTONG ROYONG SISWA SEKOLAH DASAR - Misdar, Afifah Asro Amatulloh; Supriyadi, Supriyadi (JPDI (Jurnal Pendidikan Dasar Indonesia), 2025)
This study aims to describe the application of the Project Based Learning model to strengthen the mutual cooperation character of elementary school students. The background of this research is based on the importance of instilling the value of mutual cooperation as part of elementary school character. Through a qualitative phenomenological approach by exploring the tearcher’s experience in applying the PjBL model, data were collected through in-depth. Observations made in the classroom during the learning process with the PjBL model, and documentation on teachers an grade 4 students who have applied the PjBL model in learning mathematics on the material of folding symmetry and rotary symmetry. Data analysis was conducted using the Miles an Huberman model, through the stages of data condensation, data presentation, and conclusion drawing. The results showed that the implementation of PjBL was effectively able to mutual cooperation character. Students are very actively involved in the project-based learning process, starting from the questions formulation, planning, implementation, to project evaluation collaboratively, caring, and sharing. During the process, students learn to work together, share taks, care for help friends, and respect the opinions of friends. The teacher acts as a facilitator who guides and encourages effective communication and collaboration among students. The findings of this study show that PjBL not only improves academic learning outcomes, but also shapes positive sosial attitudes, as well as caring, collaboration, and sharing. Thus, the Project Based Learning model is recommended as one of the learning strategies that can strengthen the mutual cooperation character of elementary school studends.